Proteínas e Indução Experimental da Matriz Peritrófica de Anopheles darlingi root, 1926, Principal Vetor da Malária na Amazônia, Brasil - Simões, Rejane de Castro (2010)
Proteins were analyzed and established the methodology of experimental induction of the peritrophic matrix (PM) of Anopheles darlingi in adults and larvae- Type R-Type II. In the standardization process for adults - MP Type I, it was found that the time from 10 hours after feeding, with the latex solution was sufficient for complete formation of the MP. This procedure ensured the successful extraction of the MP in order to form the full sample analysis. For larvae-MP Type II, it was found that the period of one hour was the perfect time for the formation of MP, with the power of activated charcoal. After the dissection of MP, were subjected to extraction and quantification of proteins. The proteins of the MP were analyzed by mass spectrometry. The results show the identification of proteins to eight MP of Anopheles darlingi. Similarity comparative analysis through the NCBI data base showed that ADP1, AdP3, AdP4, AdP6, AdP7, AdP8 proteins were identified in Anopheles gambiae, AdP2 protein in Anopheles farauti; AdP5 protein in Anopheles albimanus genomes, respectively. By analogy with ontology of proteins from of Anopheles genomes already described, suggest that the proteins identified in Anopheles darlingi exhibit similar function. AdP3 and AdP5 participate in the immune response during Plasmodium invasion vector of the parasite.